2020
DOI: 10.3390/plants9091169
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Phytoene Synthase PSY1 During Fruit Carotenogenesis in Cultivated and Wild Tomato Species (Solanum section Lycopersicon)

Abstract: In plants, carotenoids define fruit pigmentation and are involved in the processes of photo-oxidative stress defense and phytohormone production; a key enzyme responsible for carotene synthesis in fruit is phytoene synthase 1 (PSY1). Tomatoes (Solanum section Lycopersicon) comprise cultivated (Solanum lycopersicum) as well as wild species with different fruit color and are a good model to study carotenogenesis in fleshy fruit. In this study, we identified homologous PSY1 genes in five Solanum section Lycopersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 76 publications
(106 reference statements)
1
13
0
3
Order By: Relevance
“…In summary, the total amount of carotenoids in tomato fruits can vary depending on PSY1 expression, but the ratio of lycopene among the varieties may remain constant by controlling downstream pathways. It is known that carotenoid content in tomato fruit is largely influenced by changes in growth conditions (e.g., light, temperature, season, drought stress, salinity stress, and pedoclimatic conditions) [ 9 , 38 , 39 , 40 , 41 ]. Analyzing associations between carotenoid and AC-VOC content in tomato fruits grown under different growth conditions may reveal further clues for improving AC-VOC production.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the total amount of carotenoids in tomato fruits can vary depending on PSY1 expression, but the ratio of lycopene among the varieties may remain constant by controlling downstream pathways. It is known that carotenoid content in tomato fruit is largely influenced by changes in growth conditions (e.g., light, temperature, season, drought stress, salinity stress, and pedoclimatic conditions) [ 9 , 38 , 39 , 40 , 41 ]. Analyzing associations between carotenoid and AC-VOC content in tomato fruits grown under different growth conditions may reveal further clues for improving AC-VOC production.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated transcriptional regulation of the genes involved in carotenoid biosynthesis in tomato. Thus, it has been shown that in S. lycopersicum and S. pennellii the upstream regions of the PSY1 gene contain at least 37 types of regulatory elements, indicating that PSY1 transcription may be altered in response to light, abiotic stresses, and hormones [28,29]. Our analysis revealed that the upstream regions of Z-ISO also contained cis-elements associated with response to light, hormones, and stresses and did not significantly differ between RF S. lycopersicum cv.…”
Section: Discussionmentioning
confidence: 60%
“…The conversion of chloroplasts to chromoplasts, which store the carotenoid pigments, is essential for fruit ripening process in tomato and is the primary factor in tomato fruit coloring [34,35]. The other factor is the expression of PSY1, which catalyzes the first stage of carotenoid biosynthesis and defines the content of colored carotenoids [29]. In this scenario, Z-ISO, which determines the switch from the production of colorless carotene to that of colored carotenoids, should contribute to the difference in the color of ripe fruit between YF/RF and GF tomato species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(red fruit) [ 9 , 10 ]. The difference in fruit color between wild green-fruited (GF) tomatoes and S. lycopersicum cultivars is defined by carotenoid content [ 11 ], and that in taste by preferential accumulation of sucrose instead of glucose and fructose, respectively [ 12 ]. However, S. lycopersicum variants carrying the rin mutation are similar to GF species in fruit morphology and biochemical composition [ 2 ].…”
Section: Introductionmentioning
confidence: 99%